Efecto de las manifestaciones Sociales Estudiantiles en Colombia como Factor para el Desarrollo de la Identidad Cultural de los Jóvenes de Grado Once en el Colegio Distrital Carlo Federici IED (2019-2021) - González Pachón, Andrés Felipe (Universidad Antonio Nariño, 2023)
The various social manifestations that occurred between 2019 - 2021 meant a transcendental event in the recent history of Colombia, its echoes have been heard over time and its consequences are still observed today, despite this, understanding the impact that this has is uncertain given the number of meanings present in Colombian society